On the solvability of a nonlinear optimization problem with boundary vector control of oscillatory processes - Abdyldaeva, E.F.; Kerimbekov, A.K.; Zhaparov, M.T. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
In the paper, the solvability of the nonlinear boundary optimization problem has been investigated for the oscillation processes, described by the integro-differential equation in partial derivatives with Fredholm integral operator. It has been established that the components of the boundary vector control are defined as a solution to a system of nonlinear integral equations of a specific form, and the equations of this system have the property of equal relations. An algorithm for constructing a solution to the problem of nonlinear optimization has been developed.
Тербелмелі процестерді шекаралық векторлық басқарумен сызықты емес оңтайландыру есебінің шешімі туралы
О разрешимости задачи нелинеинои оптимизации при граничном векторном управлении колебательными процессами
Keywords: General solution; nonlinear optimization; boundary vector control; functional; optimal conditions; property of equal relations